STRATEGI PEMASARAN SEKOLAH MELALUI PELIBATAN MASYARAKAT DALAM PELAKSANAAN PROGRAM KEGIATAN SEKOLAH - Sunarni Sunarni; Maulana Amirul Adha; Ayu Rizky Amalia Agustina; Mokhamad Zulfikar Lutfi; Rusma Indri Octaviani; Septiani Eka Safitri (Program Studi Manajemen Pendidikan, 2020)
The objectives of this research are: (1) to assess the strategies used in improving public image; (2) assessing the suitability of organizational goals with the strategies used; (3) assessing the effectiveness of the organization in implementing the strategy; and (4) provide recommendations to leaders in improving the weaknesses of the strategies used. The method used in this research is a qualitative approach, with interview and observation data collection techniques. The research was conducted at SMA Panjura Malang City with the key informant, namely the principal, with the teacher as additional informants. The results of this study indicate that to improve the public image of the school is to publish about the excellence of the school. The strategy used by the school is also very suitable for the purpose of publication to attract enthusiasts to attend SMA Panjura Malang City. In addition, the strategy used for the publication program was very effective. This can be proven by the progress of the number of interested students. The community in implementing the public relations program at SMA Panjura Malang City also provides criticism and suggestions to the school so that this program can be carried out effectively and efficiently.